Utilizing Brand Audit To Develop Brand Health Sebuah Kajian Literatur - Yuniati Fransisca (Media Informasi Penelitian Kabupaten Semarang, 2023)
Marketing plays a key role in the success of an organization. However, in a situation that is turbulent, challenging, and a competitive business environment, which will also affect the marketing environment, it is becoming increasingly important for organizations to know and periodically review the effectiveness of their marketing efforts. Effective marketing starts with a well-planned marketing strategy. A good marketing strategy helps marketers define the vision, mission and business goals, so that they can outline the steps that need to be taken to achieve the vision, mission and goals. The marketing strategy that is formed will affect the way the organization runs its entire business, so it must be planned and developed properly. Marketing strategy is a broad and comprehensive strategic planning tool that describes the business, products and services, explains the position and role of products and services in the market, provides a clear picture of customer and competitor profiles, identifies marketing tactics to be used, allows the organization to create a marketing plan all at once measure its effectiveness